Integrated radio‐frequency/wireless coil design for simultaneous MR image acquisition and wireless communication. Issue 3 (14th September 2018) - Darnell, Dean; Cuthbertson, Jonathan; Robb, Fraser; Song, Allen W.; Truong, Trong‐Kha
Abstract : Purpose: An innovative radio‐frequency (RF) coil design that allows RF currents both at the Larmor frequency and in a wireless communication band to flow on the same coil is proposed to enable simultaneous MRI signal reception and wireless data transfer, thereby minimizing the number of wired connections in the scanner without requiring any modifications or additional hardware within the scanner bore. Methods: As a first application, the proposed integrated RF/wireless coil design was further combined with an integrated RF/shim coil design to perform not only MR image acquisition and wireless data transfer, but also localized B 0 shimming with a single coil. Proof‐of‐concept phantom experiments were conducted with such a coil to demonstrate its ability to simultaneously perform these three functions, while maintaining the RF performance, wireless data integrity, and B 0 shimming performance. Results: Performing wirelessly controlled shimming of localized B 0 inhomogeneities with the coil substantially reduced the B 0 root‐mean‐square error (>70%) and geometric distortions in echo‐planar images without degrading the image quality, signal‐to‐noise ratio (<1.7%), or wireless data throughput (maximum variance = 0.04 Mbps) of the coil. Conclusions: The RF/wireless coil design can provide a solution for wireless data transfer that can be easily integrated into existing MRI scanners for a variety of applications.